Konsepsi Alam Semesta dalam Al-Qur’an: Kajian Teologis dan Saintifik - Nelsa Ondiana; M. Ilham Febriansyah; Alihan Satra (Advances In Education Journal, 2026)
The universe and all its contents certainly did not come into being on their own. The universe is one of the signs of Allah SWT’s greatness that is frequently discussed in the Qur’an. Various verses explain the creation, order, and function of the universe as a means for humans to come to know the Creator. This study aims to analyze the conception of the universe from the perspective of the Qur’an, examine the process of the universe’s creation according to Qur’anic verses and Hadith, explore the meanings contained in verses related to the creation of the universe, and identify the relationship between humanity and the universe from an Islamic perspective. The method used in this study is a literature review method involving the utilization of available resources from various sources such as books, journals, and academic databases, for example, Google Scholar. The results of this study indicate that the universe, from the perspective of the Qur’an, serves as evidence of the greatness and power of Allah SWT, which is full of order, and as a means of imparting knowledge to humanity for the proper management of nature.